2020
DOI: 10.1021/acs.langmuir.0c01230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strain and Kinetics on the H2O2-Assisted Reconstruction of Ag–Au–Ag Nanorods

Abstract: Morphology of Ag nanocrystals (NCs) is essential to the NC application in catalysis, optics, and as antibacterial agents. Therefore, it is important to develop synthetic methods and understand the evaluation of NC morphology in different chemical environments. In this study, we report interesting findings of the morphological change of fivefold-twinned Ag–Au–Ag nanorods (NRs) under the effect of H 2 O 2 both as an oxidant (etchant) and a reductant. At low H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Nonetheless, the peak intensity still has 67% of the initial intensity after 30 days (Figure D). On the contrary, pure Ag colloids had only 40% of the initial intensity after 30 days in air . The above tests on sensitivity, uniformity, reproducibility, and stability demonstrate that the SERS paper chip exhibits great potential in practical applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the peak intensity still has 67% of the initial intensity after 30 days (Figure D). On the contrary, pure Ag colloids had only 40% of the initial intensity after 30 days in air . The above tests on sensitivity, uniformity, reproducibility, and stability demonstrate that the SERS paper chip exhibits great potential in practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with individual plasmonic SERS substrates, the introduction of semiconductor oxides improves the SERS sensitivity from the charge transfer (CT) effect, as well as the EM effect. Meanwhile, semiconductor oxides have a stronger ability to adsorb analytes than plasmonic metals. Moreover, since the nanogaps in SERS substrates can provide abundant “hotspots,” multilayered nanostructures with controllable nanogaps can generate the coupling of mutual polariton modes. Hao et al reported that 5-fold-twinned Ag–Au–Ag nanorods (NRs) had an enhancement factor (EF) of 9.0 × 10 5 for SERS detection of 2-naphthalenethiol. Zha et al synthesized a Ag-multilayer-Au film with a limit of detection (LOD) of 10 –13 M for rhodamine 6G (R6G) detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with an individual component cocatalyst, the surface properties and electronic structure of alloy are tailored, which displays different CO 2 adsorption behavior and steers the d‐band centers of active sites, thus possessing great potential in improving the activity and selectivity of photocatalytic CRR 148,149 . For instance, as for PdCu alloy, Pd mainly works on water adsorption and activation, while Cu prefers to adsorb and activate CO 2 molecules in CRR 107 .…”
Section: State‐of‐the‐art Strategies For Synthesizing Highly Active G...mentioning
confidence: 99%
“…Compared with an individual component cocatalyst, the surface properties and electronic structure of alloy are tailored, which displays different CO 2 adsorption behavior and steers the d-band centers of active sites, thus possessing great potential in improving the activity and selectivity of photocatalytic CRR. 148,149 For instance, as for PdCu alloy, Pd mainly works on water adsorption and activation, while Cu prefers to adsorb and activate CO 2 107 As a result, when g-C 3 N 4 was integrated with PdCu alloy NPs through an in-situ approach, the resultant PdCu/g-C 3 N 4 composite exhibited 100% selection toward CO 2 to CH 4 conversion (Figure 19). In addition, it was found that the hydrogen amount adsorbed on Pd determines the CH 4 generation rate.…”
Section: Alloy Nps Serving As Cocatalystmentioning
confidence: 99%